An integrated network pharmacology and transcriptomic method to explore the mechanism of the total Rhizoma Coptidis alkaloids in improving diabetic nephropathy. (24th April 2021) - Xiao, Yaping; Liu, Yan; Lai, Zhihui; Huang, Jieyao; Li, Chunming; Zhang, Yaru; Gong, Xiaobao; Deng, Jianling; Ye, Xiaoli; Li, Xuegang
Abstract: Ethnopharmacological relevance: Rhizoma Coptidis (RC) is a traditional Chinese medicine (TCM) used for treating diabetes (Xiao Ke Zheng), which is firstly recorded in Shennong Bencao Jing . Modern pharmacological studies have confirmed that RC has beneficial effects on diabetes and its complications. Alkaloids are the main active pharmacological component of RC. However, the effect and molecular mechanism of total Rhizoma Coptidis alkaloids (TRCA) in improving diabetic nephropathy (DN) are still unclear. Aim of the study: To verify the effect of TRCA in the treatment of DN and clarify the molecular mechanism by combining network pharmacology and transcriptomic. Materials and methods: Eight-week-old db/db mice were orally administered with normal saline, 100 mg/kg TRCA, and 100 mg/kg berberine (BBR) for 8 weeks. Serum, urine, and kidney samples were collected to measure biological indicators and observe renal pathological changes. Then, the molecular mechanism of TRCA improving DN was predicted by the network pharmacology. Briefly, the main active alkaloids components of TRCA and their targets were collected from the database, as well as the potential targets of DN. Using the Cytoscape software to visualize the interactive network diagram of "ingredient-target". The GO and KEGG pathways enrichment analysis of the core targets were executed by Metascape. Furthermore, RNA-seq was used to get whole transcriptomes from the kidneys of db/m mice, db/db mice, and db/db mice treated with TRCA. The key differentially expressed genes (DEGs) were gathered to conduct the GO and KEGG pathways enrichment analysis. Finally, the potential pathways were validated by western blotting. Results: The administration of BBR or TRCA for 8 weeks significantly reduced the fasting blood glucose (FBG) and body weight of db/db mice, and improved their renal function and lipid disorders. According to H&E, PAS, and Masson staining, both the BBR and TRCA could alleviate renal damage and fibrosis. The Venn diagram had shown that seven alkaloids ingredients collected from TRCA regulated 85 common targets merged in the TRCA and DN. The results of RNA-seq indicated that there are 121 potential targets for TRCA treatment on DN. Intriguingly, both the AGE-RAGE signaling pathway and the PI3k-Akt signaling pathway were included in the KEGG pathways enrichment results of network pharmacology and RNA-seq. Moreover, we verified that TRCA down-regulated the expression of related proteins in the AGEs-RAGE-TGFβ/Smad2 and PI3K-Akt pathways in the kidney tissues. Conclusions: In summary, the renal protection of TRCA on DN may be related to activation of the AGEs-RAGE-TGFβ/Smad2 and PI3K-Akt signaling pathways. Graphical abstract: Image 1